Making maps in powerpoint and word: Why do regional scientists not map their results? - Thomas Vanoutrive (European Regional Science Association (ERSA), 2010)
Cartography has commonly been used in regional science, and Exploratory Spatial Data Analysis is regularly applied to visualise the distribution of the variable of interest in space. Articles often contain several maps of administrative areas showing the values of a certain variable. However, and despite the benefits of such maps, they are nothing more than spatial catalogues of data. Their usefulness for regional scientist is beyond questioning, but the communicative value is limited. The rise of GIS has rightly been welcomed by many scientists. However, critical cartographers often pose the question if 'GIS has killed cartography?'. Moreover, this discussion about maps in regional science can be more than a trivial item since it can reveal the fear of scientists to draw a conclusion. The chorematics approach, as developed by Brunet, considers maps as 'vitrines', and not as catalogues. In this paper we show that such an approach can enrich regional science by delivering a methodology to visualise spatial structures and dynamics using geometric figures. Finally, we argue that word and powerpoint are more appropriate cartographic tools than most GIS packages.
Keywords: 330